An implicit periodic nonlinear model for evaluating dynamic response of damaged slab track involving material nonlinearity of damage. (10th February 2019) - Yang, Xinwen; Shu, Yao; Zhou, Shunhua; He, Chao; Di, Honggui
Highlights: A novel periodic nonlinear model with implicit solving method for the damaged slab track. An efficient implicit dynamic integration scheme based on the Newmark-β method and the Newton-Raphson method. An efficient updating method for generalized internal force and tangent stiffness matrix in pseudo-spectral method. Abstract: In order to evaluate the vibration response of the slab track with damage more efficiently in high speed railway, a periodic nonlinear dynamic model with implicit solving method for damaged slab track is proposed involving the damage constitutive relationship of concrete under uniaxial tension. The vibration equations of the nonlinear model are discretized via the periodic spectral method in space domain, and subsequently based on the Newmark- β method and the Newton-Raphson method, the implicit dynamic integration scheme is constructed in time domain. The detailed solving procedure of the implicit dynamic integration scheme with Newton-Raphson iteration for the periodic nonlinear model is illustrated ultimately. By comparing the implicit and explicit solutions of the periodic model, the correctness and efficiency of the periodic model are verified. Furthermore, the vibration response and the evolutional rules of structural damage for the slab track of high speed railway with different strength grades for concrete slab are investigated respectively via employing the periodic model with implicit solving method.